2018
DOI: 10.1029/2018gl077511
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Duration and Continuity of Potential Climate Records From the Allan Hills Blue Ice Area, East Antarctica

Abstract: The current ice core record extends back 800,000 years. Geologic and glaciological evidence suggests that the Allan Hills Blue Ice Area, East Antarctica, may preserve a continuous record that extends further back in time. In this study, we use ice-penetrating radar and existing age constraints to map the internal stratigraphy and age structure of the Allan Hills Main Ice Field. The dated isochrones provide constraints for an ice flow model to estimate the age of ice near the bed. Previous drilling in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…(neglecting the effect of wind, which removes lighter and smaller fragments much more quickly; Benoit and Sears, 1999;Folco et al, 2002). It is crucial to note that this surface residency time scale does not necessarily equate with a meteorite's terrestrial age (i.e., the duration of time since that meteorite arrived on Earth), which is likely to be far greater for englacial samples (Kehrl et al, 2018).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…(neglecting the effect of wind, which removes lighter and smaller fragments much more quickly; Benoit and Sears, 1999;Folco et al, 2002). It is crucial to note that this surface residency time scale does not necessarily equate with a meteorite's terrestrial age (i.e., the duration of time since that meteorite arrived on Earth), which is likely to be far greater for englacial samples (Kehrl et al, 2018).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Furthermore, blue ice areas have the potential to contain surface or shallow ice that is older than that recovered from deep drilling projects and can in some cases provide a higher temporal resolution (e.g. Sinisalo et al, 2007;Higgins et al, 2015;Bibby et al, 2016;Kehrl et al, 2018). Equally important, ice is available in large quantities, which is necessary for certain types of measurements, such as the characterization of trapped gasses and their isotopic composition (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, regardless the cause(s) of the LIG spike in S27 accumulation rate, it has significant glaciological implications in terms of ice flow modeling for the Allan Hills BIA, where ice older than 2 million years (Ma) has been discovered in sites disconnected from the main ice flow line (Yan et al, 2019). Recent ice-penetrating radar surveys and ice flow modeling by Kehrl et al (2018) have suggested the potential preservation of a stratigraphically continuous ice record, with 1 Ma ice located 25 to 35 m above the bedrock. The modeling efforts by Kehrl et al (2018) assume no-higher-than-present accumulation rates in the past and constant sublimation rates that control the exhumation of ice along the flow line.…”
Section: Discussionmentioning
confidence: 99%
“…Recent ice-penetrating radar surveys and ice flow modeling by Kehrl et al (2018) have suggested the potential preservation of a stratigraphically continuous ice record, with 1 Ma ice located 25 to 35 m above the bedrock. The modeling efforts by Kehrl et al (2018) assume no-higher-than-present accumulation rates in the past and constant sublimation rates that control the exhumation of ice along the flow line. In light of the discovery of this work, models with the time-dependent accumulation rate constrained by observations could better predict the age-depth profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation